The WEFE nexus and One Health: Complex links present challenges and opportunities - Lautze, Jonathan F.; McCartney, Matthew P.; Singh, Vartika (CGIAR, 2024)
To mark World Health Day 2024, this webinar discusses two case studies where the water-energy-food-ecosystems (WEFE) nexus and One Health systems overlap. The first case study links built surface water storage systems – a mainstay of the WEFE nexus – with human health, while the second assesses the WEFE nexus of the rice–fisheries system. This is followed by a discussion of the challenges and opportunities of systems approaches to achieve real impact.